Use Of Loanwords For Medical Terms In Interview With The Republic Indonesian Deputy Minister Of Health - Elfa Ali Idrus (Universitas Nahdlatul Wathan Mataram, 2024)
Health communication has a strong relationship with human efforts to maintain their health, both at the individual, group, organizational, and government levels. Government communication can be seen during an interview with the Deputy Minister of Health of the Republic of Indonesia, Professor Dante Saksono Harbuwono, on the topic